The habitat preferences of invasive raccoon dog imply elevated risks for wetland-associated prey species - Toivonen, Pyry; Laaksonen, Toni; Piironen, Antti; Selonen, Vesa (SPRINGER, 2025)
Habitat preferences of invasive predators determine where and for which prey species they pose a threat upon. This is crucial information for the conservation of endangered prey species because invasive predators pose additional predation on top of that caused by natural predators. In large parts of Europe, the most common invasive mesopredator is the raccoon dog (Nyctereutes procyonoides). To understand the risk that the raccoon dog poses for wetland-associated species, we collected information about its habitat preferences near these habitats. We used data on 24 GPS-collared raccoon dogs from three landscape types in Finland, to study their spatial and temporal habitat preferences. We first determined their home ranges, within which we then examined habitat use and preferences. Raccoon dogs showed generalist habitat use, which was evident in their wide range of used habitats. However, in spring and summer, during the breeding seasons of waterfowl and amphibians, they preferred wetlands and peatlands. They also preferred shorelines and the edges of forests and agricultural fields. During autumn and winter, raccoon dogs did not prefer wetlands. These findings support the conclusion that the raccoon dog's habitat preferences pose a particular threat to wetland-associated species, such as nesting waterfowl and amphibians. The species' habitat preferences coupled with high numbers of this invasive mesopredator pose additional predation for endangered wetland-associated species on top of that of native predators.